Makan dan Makanan dalam Yahudi dan Islam: Mempertemukan Kashrut dan Halal-Haram - Gultom, Harry Brilianto (LP2M UIN Sunan Kalijaga, 2023)
This article aims to explore the similarities and intersections between Judaism and Islam. Both Judaism and Islam are religions of law that regulate all aspects of their adherents' lives. One of the doctrines (thoughts) of both religions that have similarities and can be dialogued is food. For both religions, food is a critical element in religious teaching. Judaism and Islam each have rules that determine which foods are permissible and which are not. The determination of these foods certainly has its own rationale. Therefore, to understand the reasoning behind the food determinations in both religions, an exploratory method will be used through library research. In conclusion, it will be revealed that Judaism and Islam find common ground in determining which foods are permissible and impermissible, with the intent to maintain the distinctiveness, integrity, and devotion of the followers to their deity. [Artikel ini bertujuan melihat perbandingan dan titik temu antara ajaran agama Yahudi dan agama Islam. Baik agama Yahudi dan agama Islam keduanya adalah agama hukum yang mengatur segala aspek kehidupan umatnya. Salah satu ajaran dari kedua agama yang memiliki persamaan dan dapat didialogkan adalah hal makanan. Bagi kedua agama, makanan adalah unsur yang sangat penting dalam ajaran agama. Agama Yahudi dan dan agama Islam masing-masing memiliki aturan yang menentukan apa saja makanan yang boleh dikonsumsi dan makanan yang tidak boleh dikonsumsi. Penentuan makanan itu tentu memiliki alasan tersendiri. Maka untuk mendapatkan alasan penentuan makanan bagi kedua agama, metode yang akan digunakan adalah eksploratif melalui penelitian kepustakaan (library research). Pada akhirnya akan disimpulkan bahwa agama Yahudi dan agama Islam memiliki titik temu dalam penetapan makanan yang boleh dan tidak boleh dimakan yakni untuk menjaga kekhususan, keutuhan, dan ketaatan umat kepada yang dipujanya.]